2002
DOI: 10.1111/1467-6486.00281
|View full text |Cite
|
Sign up to set email alerts
|

Battle in the Boardroom: A Discursive Perspective

Abstract: This article examines the centrality of storytelling in achieving managerially relevant outcomes, with a focus on the in-situ performance context of corporate storytellers influencing one another. The Ricoeurian concept of speech act, capturing both the intentionality of organisational discourse and the social context of its production and reception, implicitly guided our research effort. The article has at its core a story of how senior organizational officers exploited the volatile circumstances of a major p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 40 publications
(54 reference statements)
3
37
0
1
Order By: Relevance
“…However, it is also possible that the rhetoric in these public documents is a façade, and does not reflect the power struggle and conflicting accounts of the transaction behind the scenes, as Ng and de Cock (2002) found in their analysis of one hostile bid.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also possible that the rhetoric in these public documents is a façade, and does not reflect the power struggle and conflicting accounts of the transaction behind the scenes, as Ng and de Cock (2002) found in their analysis of one hostile bid.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the chair and the CEO is widely recognised as important, especially for effective board performance (Burton 2000;Ng and De Cock 2002). The main underpinning of effective chairÁCEO relationships appears to be 'psychological closeness' (Jones 1995).…”
Section: The Role Of the Board Chair In Non-educational Settingsmentioning
confidence: 99%
“…Being an exploratory study, the privileged, insider information that some refer to as "the behind-closed-doors stuff" (Coombes and Wong, 2004), "black-box of boardroom deliberation" (Daily et al, 2003) or being privy to the "inner sanctum", or "inner shown that personal narratives can provide a rich source of data concerning the ways individuals frame social experiences in order to pursue inquiry of socially constructed organisational processes (Ng and De Cock, 2002).…”
Section: The Studymentioning
confidence: 99%